HERBAL INFUSIONS AS INHIBITORS OF TRYPSIN ACTIVITY IN WATER AND POLAR ORGANIC SOLVENT–WATER SYSTEMS (Proceedings of the YSU B: Chemical and Biological Sciences, 2023)
The inhibition of digestive enzyme trypsin by polyphenolic compounds derived from mountainous herbal infusions, as well as the effect of polarity and acidity of the media on this process were studied by virtue of UV-Vis absorption spectroscopy at 293.15 K. Mountainous herbal infusions (thyme, peppermint) are well known due to their biomedical significance and wide use as a beverage. The binding constant (Kb) and standard Gibbs energy change (ΔG0) were calculated. The obtained results show that polyphenols extracted from herbal infusions significantly inhibit trypsin. Moreover, the effect of thyme infusion is stronger compared with that of peppermint. The results show that the change of both polarity and H-bonding ability of polar organic cosolvent significantly alters the value of Kb, indicating that H-bonds and electrostatic interactions are the main driving forces in these interactions.
Keywords: trypsin; polyphenolic compounds; thyme infusion; peppermint infusion; polar organic cosolvent; acidic media